Tevhid ve Sünnet Cemaati as an Islamic social movement - Özkul, Mehmet Özgün. (Thesis (M.A.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2021., 2021)
This thesis examines the formation of Salaϐi identity in Tevhid ve Sünnet Cemaati, an Islamic group that was founded by Halis Bayancuk aka Ebu Hanzala in 2007 Turkey, by focusing on the role of culture in mobilizing and motivating individuals. This study analyzes Tevhid ve Sünnet Cemaati within the framework of social movements theory. The research emphasizes three focal points that are practices, text and materiality. To reveal how collective identity shapes individuals and is shaped by them through these three focal areas, a field research was conducted in Bağcılar where the group’s main setting is located. Participant observa tion and informal interviewing were used to highlight how particular re ligious doctrines are interpreted by the group adherents and put into practice in their daily lives. In this regard, the doctrine of al-wala’ wa-l bara is a significant concept since it separates the outside world as us and them. The doctrine, concerning the perception of reality, encourages be lievers to show loyalty to Muslims only and disavowal to non-Muslims. This thesis also argues that the group adopts various tactics and strate gies in changing circumstances, and targets existing moral/cultural val ues, political regimes by producing frames and counter-frames depend ing on its Salafi identity.
Keywords: Salafīyah -- Political aspects -- Turkey.; Islam and politics -- Turkey.